2019
DOI: 10.1136/bjsports-2018-100002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of time-loss injuries in international fencing: a prospective, 5-year analysis of Fédération Internationale d’Escrime competitions

Abstract: ObjectivesThe study aimed to determine the risk of time-loss injuries in international fencing and to characterise their type, location, severity and mechanism. Variations in risk associated with sex and discipline categories are also examined.MethodsData on participation and withdrawal due to injury from 809 competitions comprising the major events of the 2010–2014 seasons (inclusive) for the Fédération Internationale d’Escrime were compiled from official results. Athletes who withdrew due to injury sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
9
1
1
Order By: Relevance
“…However, it is not always the case. In relation to fencing, it is found that senior athletes experience more injuries than any other age class, but there is no significant influence between age and injury incidence 3 .…”
Section: Intrinsic Risk Factorsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, it is not always the case. In relation to fencing, it is found that senior athletes experience more injuries than any other age class, but there is no significant influence between age and injury incidence 3 .…”
Section: Intrinsic Risk Factorsmentioning
confidence: 93%
“…This study has concluded that knee pain and injury history are associated with new knee injuries. 10 In relation to fencing, Harmer 3 states that intensification of the injury history is associated with 27.6% of recorded injuries. In line with that, Prakash and Sinha 6 have found that out of 14 injured athletes, 28.5% have previous injuries.…”
Section: Intrinsic Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lunge, arka taraftaki alt ekstremite plantar fleksörleri ve kalça/diz ekstansörleri ile ön taraftaki alt ekstremitede kalça fleksörleri ve diz ekstansörlerinin koordineli bir şekilde çalışmasıyla meydana gelmektedir. Lunge sırasında en çok ayak bileği plantar fleksörleri ile diz ekstansörlerinin aktivite gösterdiği ve arka taraftaki alt ekstremitede en fazla kas aktivitesinin sırasıyla plantar fleksörler, diz ekstansörleri ve kalça abduktörlerinde olduğu görülmüştür (Morris ve diğerleri, 2011 (Harmer, 2019). Ayrıca kadın eskrim sporcularında yaralanma prevalansının erkeklerden daha yüksek olduğu da belirtilmektedir (Chen ve diğerleri, 2017;Harmer, 2008 (Sinclair ve Bottoms, 2013.…”
Section: Kas Aktivitesiunclassified
“…The results of a prospective cohort investigation of university fencers found that the injury rate in 1 year was 0.243%, of which ankle injuries accounted for 25% of all injuries [ 6 ]. A study on the risk of time-loss injuries found that the injury rate of 85,686 participants was 0.028%, of which ankle sprain was the most common one, with an incidence rate of 25.3% [ 7 ]. However, taking into account the experimental approaches adopted by previous epidemiological analyses using interview and questionnaire-based techniques [ 2 , 6 ], it can be postulated that the current epidemiological literature base in fencing is insufficient [ 6 ].…”
Section: Introductionmentioning
confidence: 99%